Pengaruh Kemampuan Kerja dan Motivasi Kerja terhadap Kinerja Karyawan (Studi pada karyawan PT Makmur Sejahtera Wisesa Tanjung Tabalong - Kalimantan Selatan) - Puteri, Annisa Chateliana; , Jati Waskito, S.E., M.Si; , Lukman Hakim, S.E., M.Si (2016)
The purpose of this study was to determine the effect of working ability and motivation to work partially and simultaneously on the performance of employees of PT Makmur Sejahtera Wisesa (MSW). In this study took a sample of 55 employees with simple random sampling technique that sampling of the population was randomly without regard to strata that exist in the population. The type of data and data sources used were primary data obtained from the questionnaire answers and secondary data such as archives and literature of the company. Test instrument used in this study was to test the validity and reliability testing. Then performed classical assumption that the form of normality test, multicollinierity, and test homoskedastisitas. Methods of significance, is a multiple linear regression analysis used t test and F. The results showed thesignificant relationship between work motivation on employee performance. Form these two variables, variable working ability have the results of the t (1.189) < t table (2.007) so Ho accepted and Ha rejected. With the receipt of Ho means workability no significant influence on employee performance. While the F test obtained F count of > 16.982 F table (3.175) so that Ho refused and Ha accepted. With rejection of Ho which means simultaneously there is a significant influence of the independent variables (work ability, work motivation) on the dependent variable ( performance of employees).